Evaluasi Pelaksanaan Program Bantuan Pangan Non- Tunai (Bpnt) dengan Metode E-Warung di Kabupaten Bojonegoro Tahun 2021 (Studi Kasus di Dinas Sosial Kabupaten Bojonegoro) - Rupiarsieh Rupiarsieh; Musta’ana Musta’ana (Journal of Research and Development on Public Policy, 2023)
The poverty rate in Bojonegoro Regency in 2021 has increased by 166.52 thousand people. Therefore, it is necessary to make efforts to reduce the lives of the poor towards prosperity by means of the government taking sustainable actions to facilitate access to food. Non-Cash Food Assistance is one of the programs issued by the government, but in its implementation there are still many problems that make the program not effective enough.This study aims to find out and describe how to evaluate the implementation of the non-cash food assistance program (BPNT) using the e-shop method in Bojonegoro Regency in 2021.The research methodology uses a qualitative descriptive research method with several informants as research subjects. Data obtained by interview, observation and documentation techniques. Furthermore, the data analysis technique used is data reduction, data presentation, and drawing conclusions.The results of the study show that the Evaluation of the Implementation of the Non-Cash Food Assistance Program (BPNT) using the E-warung Method in Bojonegoro Regency in 2021 has not run optimally and has not been fully effective even though several indicators have been fulfilled quite well, such as the benefits obtained by several informants. However, there are still a number of indicators that have not been fulfilled sufficiently to hinder the success of the Evaluation of the Implementation of the Non-Cash Food Assistance Program (BPNT) using the E-warung Method in Bojonegoro Regency in 2021, namely inaccuracy in targeting aid recipients, inaccuracy in the quality of food ingredients, inaccuracy in the delivery of assistance, shortage of E-warong agents in areas that are quite far from other sub-district agents. Based on the results of the research, the researcher gave advice to the Bojonegoro Regency Social Service in the form of the need to monitor and evaluate the process of implementing assistance, and to increase the number of E-warung in various sub-districts in Bojonegoro.